33 Increasing Awareness in Paramedics Ambulance Personnel Reduces Door-to-Balloon Times. (31st May 2014) - Sharma, Divyesh; Hobson, Alexander; Griffiths, Huw; Cannaughton, Mark; Strike, Phil; Dana, Ali
Abstract : Introduction: Timely primary percutaneous coronary intervention (pPCI) has repeatedly been shown to be superior to fibrinolytic treatment in randomised control trials. The delay between first medical contact (FMC) and reperfusion ('system delay') is most readily modifiable and predicts outcome. Ambulance service has a critical role in pre-hospital diagnosis, triage and timely transfer of these patients to PCI-capable hospitals to minimise delay and optimise outcomes in STEMI patients. In this study, we evaluated the impact of a regular training program directed at paramedics on door-to-balloon times in our hear attack centre, over a 3 year period. Methods: A series of one-day training courses, directed at ambulance personnel to increase awareness, were conducted at our centre, with the principal message being that 'time is muscle'. Data on door-to-balloon (DTB) times for patients admitted via Emergency department (ED) or direct to catheterization laboratory was prospectively recorded. The DTB times for the two groups were compared and the number of patients who breeched the target DTB times was also recorded. Results: Out of the 728 patients included in the study, a total of 106 (14.6%) patients breeched the target DTB time of <90 min. The majority of these patients (n = 93; 88%) were admitted via ED for pPCI. In contrast, only 8 out of 484 patients (1.7%) who were directly admitted to the catheterisation laboratory breeched the DTB target. Following the training courses, the number of patients admitted via ED for pPCI reduced significantly with a simultaneous increase in the number of patients brought directly to the catheterisation laboratory (Figure 1 ). Overall, the median DTB time in patients who bypassed ED was significantly lower than those admitted via ED (37 min (range 17–132) vs. 83 min (range 30–292), p < 0.05). Similarly, median call-to-balloon time was significantly lower in the patients admitted directly to the catheterization laboratory as compared to patients admitted via ED (97 min vs. 144 min, p < 0.05) (Figure 2 ). Conclusion: This study demonstrates that provision of continuous education for the ambulance personnel has the potential to results in a significant reduction in delays inherent in providing a pPCI service, and improves DTB targets by bypassing ED.